Genitourinary Syndrome of Menopause: Epidemiology, Physiopathology, Clinical Manifestation and Diagnostic - Sarmento, Ayane Cristine Alves; Costa, Ana Paula Ferreira; Vieira-Baptista, Pedro; Giraldo, Paulo César; Eleutério, José; Gonçalves, Ana Katherine (Frontiers in Reproductive Health, 2021)
Genitourinary syndrome of menopause (GSM) is a term used to define a compilation of signs and symptoms arising from decreased estrogenic stimulation of the vulvovaginal and lower urinary tract. Among 27–84% of women in postmenopausal are affected for symptoms of GSM, and these can unquestionably impair health, sexual function, consequently the quality of life of these women. The main signs and symptoms of GSM include, among others, burning, irritation, vulvovaginal dryness, dyspareunia, urinary symptoms of urgency, dysuria, or recurrent urinary tract infection. The diagnosis can be made through anamnesis, questionnaires, physical exams, and, sometimes, complementary exams. Objective vaginal assessment is essential and can be complemented by using the Vaginal Health Index (VHI), Vaginal Maturation Index (VMI), or vaginal pH measurement. The acknowledgment of this condition by health professionals is crucial for its identification and proper management and exclusion of other conditions that make a differential diagnosis with it.